New Inflammatory Marker Associated with Disease Activity in Gouty Arthritis: The Systemic Inflammatory Response Index - Jiang Y; Tu X; Liao X; He Y; Wang S; Zhang Q; Qing Y (Dove Medical Press, 2023)
Yi Jiang,1,2,* Xin Tu,1,3,* Xia Liao,1,2,* Yixi He,1,2 Shunbing Wang,1,2 Quanbo Zhang,1,3 Yufeng Qing1,2 1Research Center of Hyperuricemia and Gout, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People's Republic of China; 2Department of Rheumatology and Immunology, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People's Republic of China; 3Department of Geriatrics, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People's Republic of China*These authors contributed equally to this workCorrespondence: Quanbo Zhang; Yufeng Qing, Research Center of Hyperuricemia and Gout, Affiliated Hospital of North Sichuan Medical College, Nanchong, 637000, People's Republic of China, Tel/Fax +86 08172282131, Email quanbozhang@126.com; qingyufengqq@163.comBackground: The systemic immune-inflammatory index (SII) and systemic inflammatory response index (SIRI), as novel non-specific inflammatory markers, have recently drawn attention. At present, no studies have been conducted to investigate the value of SII and SIRI in gouty arthritis (GA), so we explored their possible association with GA disease activity.Methods: The study enrolled 474 patients with acute gouty arthritis (AG), 399 patients with intercritical gouty arthritis (IG) and 194 healthy controls (HC). The differences in Monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), SII, and SIRI levels among different groups were assessed. The changes in the above indicators before and after treatment in the AG and IG groups were evaluated. Multivariate logistic regression analysis was assessed influencing factors for the acute gout attack. ROC curves were plotted to evaluate their diagnostic value for AG.Results: Compared with the IG group, the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), PLR, and incidence of hyperlipidemia in the AG group were significantly higher, and the duration of disease was significantly shorter (P < 0.05). The MLR, NLR, SII and SIRI in the AG group were significantly higher than those in the IG and HC groups (P < 0.05). Compared with baseline, decreased MLR, NLR, PLR, SII and SIRI were observed in the AG group after treatment (P < 0.05), while there was no significant difference in the IG group before and after treatment (P >  0.05). SIRI was positively correlated with ESR and CRP (P < 0.05). Multivariate logistic regression analysis result showed that duration of disease, hyperlipidemia, ESR, CRP, and SIRI were influencing factors of acute gout attack (P